2014
DOI: 10.1002/adma.201404101
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Energy Density of Polymer Nanocomposites Containing BaTiO3@TiO2 Nanofibers by Atomic‐Scale Interface Engineering

Abstract: Atomic-scale interface engineering in BaTiO3@TO2 nanofibers (TiO2 nano-fibers embedded with BaTiO3 nano-particles) leads to concurrent enhancement of electric displacement and breakdown strength in poly(vinylidene fluoride) (PVDF)-based nanocomposites. An ultrahigh energy density of ≈20 J cm(-3) is achieved with only 3 vol% nanofibers, which is by far the highest discharged energy density of PVDF-based nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
281
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(293 citation statements)
references
References 27 publications
10
281
1
1
Order By: Relevance
“…Figure 8(b) shows the caluculated energy storage efficiency with the increasing of the radius R, the energy efficiency decreases. However, the efficiency is over 95% at R = 57 nm, which is higher than that of PVDF/BTO@TO_nfs [1] 7.5% BST NWs/PVDF [8] the reported BaTiO 3 @SrTiO 3 ceramics (about 90%) [9].…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Figure 8(b) shows the caluculated energy storage efficiency with the increasing of the radius R, the energy efficiency decreases. However, the efficiency is over 95% at R = 57 nm, which is higher than that of PVDF/BTO@TO_nfs [1] 7.5% BST NWs/PVDF [8] the reported BaTiO 3 @SrTiO 3 ceramics (about 90%) [9].…”
Section: Resultsmentioning
confidence: 68%
“…The energy density of commercial dielectric capacitors is usually of the order of 1-2 J/cm 3 , far inferior to electrochemical capacitors (≈ 20 J/cm 3 ) [1]. The energy density of a dielectric material is essentially given by U= EdP , where E is the electric field and P is the polarization.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported ceramic/polymer nanocomposites with high energy density 6, 7. For example a discharge energy density of 20 J cm −3 at 646 kV mm −1 was reported for BaTiO 3 @TiO 2 core–shell fibers in a polyvinylidene fluoride polymer matrix (denoted as BaTiO 3 @TiO 2 /PVDF, where @ denotes a core–shell structure) 8. This was subsequently improved to 31.2 J cm −3 at 797.7 kV mm −1 for nanocomposites with large aspect ratio fibers as a result of their preferred orientation directions perpendicular to the external electric field 9.…”
mentioning
confidence: 99%
“…As an alternative, composite materials may be promising candidates for high-k applications. As we know, the dielectric properties of a composite will undergo signicant changes near its percolation threshold, [8][9][10][11] and numerous researches have conrmed that percolative composites are promising candidates for high-k materials with outstanding dielectric properties, such as tunable high permittivity, high dielectric strength, low loss, etc. Therefore, various strategies have been developed to obtain high-k according to percolation theory in composite materials, such as ferroelectric/polymer composites, [12][13][14] binary or ternary metal (or carbon)/polymer composites, [15][16][17] metal (or carbon)/ ceramic composites, etc.…”
Section: Introductionmentioning
confidence: 99%